Analisis Media Sosial Isntagram Berbau Coal Sebagai Media Komunikasi Dalam Meningkatkan Engagement Publik - Fredy, Tiffany; Vanel, Zon (Jurnal Ilmiah Wahana Pendidikan, 2025)
PT Berau Coal utilizes social media as a communication tool to strengthen relationships with the public and increase interaction or engagement. This research aims to explain the company's communication strategy through Instagram to increase public engagement. This study uses a research method that combines quantitative and qualitative approaches or a mixed method with sequential explanatory designs. Data collection techniques are surveys or questionnaires, observations, interviews, and documentation. The analysis in this study uses the Circular Model of Several concepts, including Share, Optimize, Manage, and Engage. The results show that in the Share stage, PT Berau Coal has successfully identified Instagram as the main platform for sharing content based on audience preferences and high-reach data. Then, in the Optimize and Manage stages, PT Berau Coal has demonstrated a solid commitment to visual consistency and branding. The consistent use of the company's signature colors, fonts, logo, watermark, and hashtags has successfully built a strong and easily recognizable brand identity. On the other hand, PT Berau Coal's Engage strategy focuses on collaborating with strategic accounts such as local media and ministries, which is the engagement implemented by PT. Berau Coal is doing this through collaboration with the Ministry of Energy and Mineral Resources and regional media.